Mechanisms and Therapeutic Prospects of Diabetic Cardiomyopathy Through the Inflammatory Response - Kaur, Namrita; Guan, Yingshu; Raja, Rida; Ruiz-Velasco, Andrea; Liu, Wei (Frontiers in Physiology, 2021)
The incidence of heart failure (HF) continues to increase rapidly in patients with diabetes. It is marked by myocardial remodeling, including fibrosis, hypertrophy and cell death, leading to diastolic dysfunction with or without systolic dysfunction. Diabetic cardiomyopathy (DCM) is a distinct myocardial disease in the absence of coronary artery disease. DCM is partially induced by chronic systemic inflammation, underpinned by a hostile environment due to hyperglycemia, hyperlipidemia, hyperinsulinemia and insulin resistance. The detrimental role of leukocytes, cytokines and chemokines is evident in the diabetic heart, yet the precise role of inflammation as a cause or consequence of DCM remains incompletely understood. Here, we provide a concise review of the inflammatory signaling mechanisms contributing to the clinical complications of diabetes-associated HF. Overall, the impact of inflammation on the onset and development of DCM suggests the potential benefits of targeting inflammatory cascades to prevent DCM. This review is tailored to outline the known effects of the current anti-diabetic drugs, anti-inflammatory therapies, and natural compounds on inflammation, which mitigate HF progression in diabetic populations.